Chronic. Chronique. Chronic - Granja, Lucia [UNESP] (Assoc Nac Pos-graduacao Pesquisa Letras & Linguistica, 2015)
This article analyzes some characteristics concerning the rise of the Brazilian serial columns [cronica] in the nineteenth century. One of the main concerns is the analysis of the issue and occupation of space in newspaper's pages. We focus also on indicating cultural exchanges and showing that the studies of serial columns must consider the relationships between American and European countries, as well as the inter-American movements and their importance to the process of establishing newspapers and journalistic forms in Brazil and America during the nineteenth's. As an example of this cultural process, we analyze one of the effects of this textual genre adapted to the bottom of the pages of Brazilian daily newspapers, indicating, in conclusion, some points of comparison about the rise of serial columns in American Spanish-speakers countries.
Keywords: Serial columns; Literary journalism; Brazil; France; Latin-America